Representing Mental Health in Chase Atlantic’s Song Lyrics and Its Implications for English Language Teaching - Idelia Salsabillah; Yanti Rosalinah (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2026)
This study examines the representation of mental health in Chase Atlantic’s lyrics through emotional, psychological, and cultural dimensions, with a particular focus on its implications for literature teaching, critical reading, and cultural awareness in English Language Teaching (ELT). While previous studies have primarily explored the psychological effects of music on listeners, limited attention has been given to the representation of mental health in alternative R&B lyrics and its educational relevance. Using qualitative content analysis grounded in cultural representation theory, this study analyzes four songs “Consume”, “Swim”, “Stuckinmybrain”, and “Heaven and Back”. To identify recurring themes and symbolic representations of mental health. The findings reveal four dominant themes: emotional vulnerability, self-destruction and escapism, internal conflict and overthinking, and emotional resilience, reflecting the complexity of youth experiences related to anxiety, identify formation, and emotional struggle. The findings suggest that music functions not only as a form of artistic expression but also as a potential pedagogical resource for supporting crtitical literacy, cultural awareness, and reflective discussion in educational settings. This study highlights the relevance of Chase Atlantic’s lyrics as contemporary texts that may be utilized in ELT and literature classrooms to encourage engagement with issues related to mental health and cultural representation.